Reliability and validity of head posture assessment by observation and a four-category scale - Silva, A. G.
Head posture (HP) is assessed as part of the clinical examination of patients with neck pain using observation and qualitative descriptors. In research, HP is characterised through the measurement of angles and distances between anatomical landmarks. This study investigated whether the assessment of HP as performed in clinical practice is reliable and valid. Ten physiotherapists assessed forward HP, head extension and side-flexion from images of 40 individuals with and without previous experience of neck pain using a four-category scale. The assessment was repeated twice with a 1-week gap. Physiotherapists' ratings were then compared with angular measurements of the same components of HP. K values for intra-rater reliability varied between 0.22 and 0.81 for forward HP, between 0.19 and 0.69 for head extension and between 0.38 and 0.67 for side-flexion. K values for inter-rater reliability were 0.02 for forward HP, 0.07 for head extension and 0.19 for side-flexion. Correlation coefficients between the ratings and the angular measurements varied between -0.16 and -0.49 for forward HP, between -0.17 and 0.68 for head extension and between -0.04 and 0.37 for side-flexion. The assessment of HP by observation and a four-category scale showed poor reliability and validity. (C) 2010 Elsevier Ltd. All rights reserved.